DOES EMPLOYEE ENGAGEMENT MEDIATE WELL-BEING? A STUDY ON FEMALE EMPLOYEES AT THE MINISTRY OF POPULATION AND FAMILY DEVELOPMENT - Irma Ahmad; Siti Safaria (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
The well-being of female employees in the public sector is critical due to dual professional and domestic responsibilities that affect organizational productivity. This study examines the mediating role of employee engagement in the relationships between work-life balance, perceived organizational support (POS), and the well-being of female employees at the Ministry of Population and Family Development. A quantitative explanatory design was employed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Data from 100 female employees were collected via Likert-scale questionnaires and analyzed with SmartPLS 3.2.7. Results indicate that work-life balance significantly and positively influences employee engagement (β=0.599; p=0.000) and well-being (β=0.608; p=0.001). POS significantly affects employee engagement (β=0.391; p=0.000) but not well-being (β=0.167; p=0.051). Employee engagement has no significant effect on well-being (β=0.185; p=0.272) and does not mediate the relationships between work-life balance and well-being (β=0.111; p=0.296) or POS and well-being (β=0.072; p=0.277). Organizations should prioritize flexible work policies and gender-specific support to enhance well-being and productivity